Effect of Arthroscopic Acromioplasty Combined with Rotator Cuff Repair in the Treatment of Aged Patients with Full-Thickness Rotator Cuff Tear and Rotator Cuff Injury - Shihui He; Hao Xu; Shuhua Liu (Emergency Medicine International, 2022)
Full-thickness rotator cuff tear and rotator cuff injury are frequently occurring diseases and widely exist in the social population. Surgical repair is the most effective treatment for rotator cuff tears and injuries. With the continuous development of arthroscopy, more and more surgeons choose arthroscopic acromioplasty plus rotator cuff repair for the treatment of rotator cuff injury. However, previously published systematic reviews or meta-analyses still cast doubt on the efficacy of such concomitant procedures for postoperative patient function and pain recovery. In this study, we analyzed the effects of parameters such as shoulder function and acromion morphology on aged patients with full-thickness rotator cuff tear combined with rotator cuff injury treated with arthroscopic acromion plasty and rotator cuff repair. The results showed that arthroscopic acromion plasty and rotator cuff repair helped to promote the joint function recovery of the aged patients with full-thickness rotator cuff tear combined with rotator cuff injury and alleviate the pain of the patients. Compared with simple rotator cuff repair, this technique can increase the postoperative AT and reduce the ACEA and to some extent reduce the risk of postoperative rotator cuff reinjury, which is worthy of promotion.